Paediatric cranial ultrasound: assessment of the preterm brain - Caoilfhionn Ní Leidhin; Michael Paddock; Paul M. Parizel; Richard R. Warne; Peter Shipman; Rahul Lakshmanan (Insights into Imaging)
Abstract Cranial ultrasound is an invaluable tool in assessing neonatal brain anatomy and pathology. It is accessible, relatively quick, inexpensive, safe, portable and generally well-tolerated. This pictorial review focuses on the use of cranial ultrasound in evaluating the premature brain. We illustrate the different grades of intraventricular haemorrhage, the most common sequela of prematurity, its evolution and potential complications, as well as periventricular leukomalacia. Anatomical variants and benign findings that mimic preterm brain injury are also discussed. Critical relevance statement Cranial US is an invaluable tool for assessing neonatal brain anatomy and pathology and can be used in preterm infants to diagnose, monitor and assess for complications of intraventricular haemorrhage and periventricular leukomalacia. Key Points Cranial US (CUS) is an invaluable tool for assessing the neonatal brain and has many advantages over MRI. CUS can detect intraventricular haemorrhage and periventricular leukomalacia, the most important sequelae of prematurity. Knowledge of optimal CUS technique, normal anatomy, and variants/benign sonographic findings that mimic pathology is crucial to avoid misdiagnosis and unnecessary concern. Graphical Abstract